Understanding Chinese people towards Takaful product in Johor Bahru branch / Aimiliana Wahab - Wahab, Aimiliana (Faculty of Business and Management, 2010)
This research is about a study of the understanding Chinese people towards Takaful product. For indicate agent role’s, service quality and product itself used to identify the understanding Chinese people towards Takaful product is. The agent roles consist of knowledge, experiences and tactic to attract. Next, service quality consist of conducive environment, trust & confidence and expertise. Furthermore product it ‘Self consist of cost & benefit, high returns and saving. The survey is conducted in Off Jalan Tun Abdul Razak. The sample size for this study is 150 respondents. This study tries to investigate this issue by conducting a preliminary study on the level of knowledge and understanding Chinese people in Malaysia towards the Takaful product. There were 150 questionnaires being distributed and 150 were return and complete. Data obtained using three methods that are secondary data, survey and observational and other data. Respondents are required to answer the questionnaires that contain element that needed for the research. Data are analyzed using Reliability Test, Pearson Correlation Analysis, Frequency Analysis, and Descriptive Statistics through SPSS system. The result shows that what actually the most factors influences in understanding Chinese people towards Takaful product.